2015
DOI: 10.3389/fnbeh.2015.00328
|View full text |Cite
|
Sign up to set email alerts
|

Social Facilitation of Cognition in Rhesus Monkeys: Audience Vs. Coaction

Abstract: Social psychology has long established that the mere presence of a conspecific, be it an active co-performer (coaction effect), or a passive spectator (audience effect) changes behavior in humans. Yet, the process mediating this fundamental social influence has so far eluded us. Brain research and its nonhuman primate animal model, the rhesus macaque, could shed new light on this long debated issue. For this approach to be fruitful, however, we need to improve our patchy knowledge about social presence influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…Generally, digging frequencies were higher if the partner was visible, which might suggest social facilitation. However, contrasting to predictions of social facilitation theory (Sanders, 1981;Reynaud et al, 2015), coordination in frequency was negative if the partner was visible, as outlined above. Temporal coordination occurred within short time intervals, whereas no correlations in total digging frequencies were found when longer time periods were considered (10 min).…”
Section: Discussioncontrasting
confidence: 83%
“…Generally, digging frequencies were higher if the partner was visible, which might suggest social facilitation. However, contrasting to predictions of social facilitation theory (Sanders, 1981;Reynaud et al, 2015), coordination in frequency was negative if the partner was visible, as outlined above. Temporal coordination occurred within short time intervals, whereas no correlations in total digging frequencies were found when longer time periods were considered (10 min).…”
Section: Discussioncontrasting
confidence: 83%
“…A century of social psychology has built a robust knowledge about the principles ruling this fundamental form of social influence. The main ones are that others influence behavior whether their presence is actual or imagined, whether they are familiar or unknown, co-actors doing the same task or passive spectators, and whether they are evaluative or neutral (Bond and Titus, 1983;Guerin, 2010;Reynaud et al, 2015). Two issues remain unsolved though: first, the mechanism mediating social facilitation and second, the factors which make an individual more or less susceptible to others' presence.…”
Section: Introduction Social Presence Effects On Performancementioning
confidence: 99%
“…Although Allport 1 did not distinguish the social situation (co-action or the mere presence of another), it has been shown that the mere presence of other(s) affects one's performance speed or frequency 3,4,5,6 . Additionally, in animals, the mere presence of other conspecific results in a higher response rate or higher response speed during a lever-press task in rats 7,8 and higher response rate in rhesus monkeys during a simple cognitive task 9 .…”
Section: Introductionmentioning
confidence: 99%